Hyaluronic acid: A promising mediator for periodontal regeneration - Bansal Jyoti; Kedige Suresh; Anand Samir (Wolters Kluwer Medknow Publications, 2010)
Hyaluronic acid (HA) is a natural-non sulphated high molecular weight glycosaminoglycan that forms a critical component of the extracellular matrix and contributes significantly to tissue hydrodynamics, cell migration and proliferation. The use of HA in the treatment of inflammatory process is established in medical areas such as orthopedics, dermatology and ophthalmology. In the field of dentistry, hyaluronate has shown anti-inflammatory, antiedematous and anti-bacterial effects for the treatment of gingivitis and periodontitis. Due to its potential role in modulation of wound healing, its administration to periodontal wound sites could achieve comparable beneficial effects in periodontal tissue regeneration and periodontal disease treatment.